1999
DOI: 10.1021/jp990136n
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Picosecond Excited-States Dynamics in Isolated, Supercooled 4-(N,N-Dimethylamino)benzonitrile

Abstract: The first experimental evidence is presented for a strong coupling between electronic states in isolated, supercooled 4-(N,N-dimethylamino)benzonitrile, DMABN. In the fluorescence excitation spectrum, measured under isolated supercooled conditions, two types of transitions were found (B-type and C-type). Rotational contour analysis of the B-type bands (ππ* character) shows that there is hardly any difference between the geometries of the ground and excited states; the molecule retains its planar conformation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 37 publications
(69 reference statements)
5
36
1
Order By: Relevance
“…They also observed a partially resolved rotational band contour of the S 1 -S 0 electronic spectrum of DMABN and concluded that, in the S 1 state, the DMA group is rotated by 30°from the aromatic plane. Salgado et al 10 reported on the basis of similar laser experiments on the isolated molecule that the laser-induced fluorescence ͑LIF͒ spectrum contained two types of cona͒ tours, b-type bands that belonged to a "planar" excited state and c-type bands that belonged to a "twisted" excited state. But Saigusa et al 11 suggested on the basis of a reexamination of the low resolution spectra of DMABN-h 6 and -d 6 that all bands terminate in an S 1 state that is twisted by about 26°w ith a small 150 cm −1 barrier to planarity.…”
Section: Introductionmentioning
confidence: 99%
“…They also observed a partially resolved rotational band contour of the S 1 -S 0 electronic spectrum of DMABN and concluded that, in the S 1 state, the DMA group is rotated by 30°from the aromatic plane. Salgado et al 10 reported on the basis of similar laser experiments on the isolated molecule that the laser-induced fluorescence ͑LIF͒ spectrum contained two types of cona͒ tours, b-type bands that belonged to a "planar" excited state and c-type bands that belonged to a "twisted" excited state. But Saigusa et al 11 suggested on the basis of a reexamination of the low resolution spectra of DMABN-h 6 and -d 6 that all bands terminate in an S 1 state that is twisted by about 26°w ith a small 150 cm −1 barrier to planarity.…”
Section: Introductionmentioning
confidence: 99%
“…Some hints on the LE state structure has been gained by gas phase studies. [4][5][6] However, the molecular structure of the exited states in solution is a subject of considerable debate. Three models have recently been discussed for the charge transfer (CT) state: Grabowski et al proposed that the dimethylamino-group planarizes and twists by 90 0 7 This is the nCT model, where nCT stands for twisted intramolecular charge transfer (twisted lCT).…”
Section: Introductionmentioning
confidence: 99%
“…The DMABN is the most studied BN derivative because it is the classic model compound showing solvent‐induced dual fluorescence. Since the first observation of the dual fluorescence by Lippert et al 43, many theories have been proposed to explain this interesting behavior 44 as a consequence of its electronic states 45. In general, this phenomenon is attributed to formation of an intramolecular charge‐transfer state and concomitant rotational relaxation of the dimethylamino group about the amine‐aryl single bond 46, and this mechanism is supported by the fluorescence properties of various stereoselectively substituted DMABN derivatives 47.…”
Section: Molecules Studiedmentioning
confidence: 97%